Analisis Kesalahan Mahasiswa Berkemampuan Rendah dalam Menyelesaikan Soal Limit Ditinjau dari Perbedaan Gender - Siti Rochana; Lilia Sinta Wahyuniar; Umi Mahdiyah; Resty Wulanningrum (Jurnal Math Educator Nusantara: Wahana Publikasi Karya Tulis Ilmiah di Bidang Pendidikan Matematika, 2025)
The calculus learning process in higher education sometimes encounters many problems. One of the problems often faced is the lack of understanding of students in algebra, especially in the limit chapter. In the Informatics Engineering study program at Nusantara PGRI University, Kediri, most students still have low mathematical abilities and an unbalanced gender composition. This study aims to analyze the types of errors made by low-ability students in solving limit problems, viewed from gender differences. This type of research is descriptive qualitative research. Data were collected through diagnostic tests to identify conceptual, procedural, and computational errors as well as unstructured interviews to explore the causes of errors. The research subjects were six students with low mathematical abilities consisting of 3 male students and 3 female students from the 2024/2025 intake who were taking calculus courses. The analysis results showed that conceptual errors made by male students were 33% and female students were 55%. Procedural errors in male students were 55% and female students were 66%. Computational errors in male students were 66% and female students were 55%. The highest number of errors found in male students were computational errors, while procedural errors were more prevalent among female students. This indicates that students still have difficulty understanding the basic concept of limits and are unable to apply structured solution steps. Low-ability students still showed high error rates in conceptual, procedural, and computational aspects, with different tendencies according to gender. Poor mastery of the basic concept of limits impacts procedural and computational errors. Future research can expand the number of subjects and explore affective factors such as math anxiety and learning motivation that may influence the types of student errors.